Pengaruh Kepemimpinan Transformasional terhadap Perilaku Kerja Inovatif Penyiar Radio Kota Padang - Tespani, Jessy; Fitriana, Dewi; Bakhtiar, Bakhtiar (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
Radio is a telecommunication medium that still exists today. However, with the emergence of mastery of new information technology (New Media), it is possible that businesses engaged in this creative industry will experience setbacks. Therefore, all business people must have innovative work behavior in their employees. One important factor that can increase innovative work behavior in its employees is transformational leadership. This study aims to examine the influence of transformational leadership on the innovative behavior of private radio broadcasters in Padang City. This study uses quantitative methods with simple regression analysis. The study population consisted of 82 broadcasters from private radio stations in the city of Padang, with the totality sampling technique being used as a sample. The results of this study indicate that the level of transformational leadership is in the moderate category with a percentage of 53.7% and innovative work behavior with a percentage of 68.3% is also included in the moderate category. The results of this study also show that transformational leadership has a significant effect on the innovative work behavior of private radio broadcasters in the city of Padang with a significance (<0.01) and a contribution of 48.5%. So the conclusion in this study is that transformational leadership has a significant effect on the innovative work behavior of private radio broadcasters in the city of Padang.